Leveraging school principals to address learning loss in Indonesia through group and individual targeting - Dewi Susanti; Gautam Anand; Firda Arianti Arifin; Patrya Pratama (Asian Development Bank Institute (ADBI), 2023)
In Indonesia, COVID-19 pandemic-induced school closures led to a significant loss of learning among students, necessitating remedial learning programs. This study thus aimed to explore whether differentiated remedial teaching can improve the foundational numeracy skills of students and if the improvements would be better in schools with added individual tutoring. It also aimed to understand whether additional training of school principals would strengthen the results. After implementing four interventions in 25 primary schools to 1,545 students for eight weeks, we found that all interventions significantly improved the foundational numeracy skills of students, students in schools with added individual tutoring did better than those without the added tutoring, and teachers in schools with trained principals were more punctual in implementing the intervention.
Keywords: I21; 330; learning loss; group remedial; individual tutoring; school principal support